Survival and prognostic factors of progressive multifocal leukoencephalopathy in people living with HIV in modern ART era - Jiang, Rui; Song, Zichen; Liu, Li; Mei, Xue; Sun, Jianjun; Qi, Tangkai; Wang, Zhenyan; Song, Wei; Tang, Yang; Yang, Junyang; Xu, Shuibao; Zhao, Bihe; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Background:The incidence of progressive multifocal leukoencephalopathy (PML) in people living with HIV (PLWH) is 2%-4%. Currently, there is no effective therapeutic strategy for the treatment of PML in PLWH, resulting in a mortality of up to 50%. This study aimed to identify risk factors of death and prognostic markers in people living with HIV with PML.Methods: A retrospective cohort study of AIDS-related PML individuals was conducted from January 1, 2015, to October 1, 2022, in Shanghai, China. PLWH who were diagnosed with PML for the first time were included. Kaplan-Meier curve and Cox regression were used to analyze the survival and its predictors. Levels of inflammatory markers and immune checkpoint inhibitors in blood and cerebrospinal fluid (CSF) were measured in the prestored samples using bead-based multiplex assay Indolamine 2,3-dioxygenase was determined using ELISA.Results: Twenty of 71 subjects had initiated antiretroviral therapy (ART) before PML onset and no patients discontinued ART during this period. In total, 34 patients (47.9%) had opportunistic infections (OIs), the median CD4+ T cell count was 73.0 (33.0-149.0) cells/μL. The estimated probability of survival at six months was 78% (95% confidential intervals [CIs]:0.63-0.85). OIs, low CD4+ T cell count were associated with lower estimated six-month survival (hazard ratio 8.01, 95% CIs: 1.80-35.00, P=0.006 and 5.01, 95% CIs:1.57-16.03, p=0.007). Indolamine 2,3-dioxygenase activity in CSF of non-survivors group were higher than survivors group (p<0.05).The survival rate of AIDS-related PML in the modern ART era was higher than the survival rate a decade ago. Low CD4+T cell count, OIs, were all associated with death of individuals with AIDS-related PML. The role of IDO in AIDS-related PML warrant further investigation.